Cost and management accounting an introduction - Drury, Colin (South-Western Cengage Learning, 2011)
This international best-seller provides a clear and accessible introduction to cost and management accounting. Colin Drury's renowned authoring expertise blends theory and practice and the text encompasses all the basic topics needed on an introductory course. Now in its seventh edition, Cost and Management Accounting has been carefully updated to ensure it precisely fits the latest course and examination requirements.